Determinação do intervalo entre medições para avaliação de colônias de apis mellifera - SILVEIRA, RODRIGO DINIZ; Lana, José Tadeu de Oliveira; Campos, Lúcio Antônio de Oliveira; Cruz, Cosme Damião (Revista Ceres, 2015)
-